2008
DOI: 10.1002/pssc.200777900
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic ellipsometry and vector network analysis for determination of the electromagnetic response in two wavelength regions

Abstract: In this work, spectroscopic ellipsometry and vector network analysis are used to determine the electromagnetic response of three samples, an epoxy polymer, a sample with ferrit‐based nanoparticles in a polymer matrix and silicon, in the wavelength ranges 0.4‐30 μm and 0.75‐7.59 cm. Both methods measure amplitude and phase changes due to interaction with a sample and can be used to measure the full complex‐valued dielectric response to electromagnetic radiation. The data from the two methods show similar levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A thorough explanation of the need of materials for camouflage application and military utility of spectral design is found in Paper I [5]. Broadband studies of the optical properties of different materials are found in Paper II [6]. Studies of dynamic properties of a dye are presented in Paper III [7] and of a polymer in Paper IV [8].…”
Section: Thesis Outlinementioning
confidence: 99%
“…A thorough explanation of the need of materials for camouflage application and military utility of spectral design is found in Paper I [5]. Broadband studies of the optical properties of different materials are found in Paper II [6]. Studies of dynamic properties of a dye are presented in Paper III [7] and of a polymer in Paper IV [8].…”
Section: Thesis Outlinementioning
confidence: 99%
“…A signature management coating for optical wavelengths must therefore not interfere with the targets spectral design for radar wavelengths. 13 In most applications this means the reflectance of the coating should be very low. This can be achieved by making the coating very thin and transmissive, deposited on top of a radar absorbing coating, or by using a material with high absorption.…”
Section: Terminology and Physical Quantitiesmentioning
confidence: 99%